Regulation of Nuclear Localization and Transcriptional Activity of TFII-I by Bruton’s Tyrosine Kinase - Novina, Carl D. (American Society for Microbiology, 1999)
Bruton’s tyrosine kinase (Btk) is required for normal B-cell development, as defects in Btk lead to X-linked immunodeficiency (xid) in mice and X-linked agammaglobulinemia (XLA) in humans. Here we demonstrate a functional interaction between the multifunctional transcription factor TFII-I and Btk. Ectopic expression of wild-type Btk enhances TFII-I-mediated transcriptional activation and its tyrosine phosphorylation in transient-transfection assays. Mutation of Btk in either the PH domain (R28C, as in the murine xid mutation) or the kinase domain (K430E) compromises its ability to enhance both the tyrosine phosphorylation and the transcriptional activity of TFII-I. TFII-I associates constitutively in vivo with wild-type Btk and kinase-inactive Btk but not xid Btk. However, membrane immunoglobulin M cross-linking in B cells leads to dissociation of TFII-I from Btk. We further show that while TFII-I is found in both the nucleus and cytoplasm of wild-type and xid primary resting B cells, nuclear TFII-I is greater in xid B cells. Most strikingly, receptor cross-linking of wild-type (but not xid) B cells results in increased nuclear import of TFII-I. Taken together, these data suggest that although the PH domain of Btk is primarily responsible for its physical interaction with TFII-I, an intact kinase domain of Btk is required to enhance transcriptional activity of TFII-I in the nucleus. Thus, mutations impairing the physical and/or functional association between TFII-I and Btk may result in diminished TFII-I-dependent transcription and contribute to defective B-cell development and/or function.